The role of spatial informatics in recultivation - Béres, Csaba Zoltán (Acta Agraria Kaposváriensis, 2004)
A short summary is given in this article about the role of spatial informatics in recultivation, especially the role of monitoring systems. The common application and integration of GIS and monitoring systems promise sign cant benefits. The view-points and requirements on the basis of which the development of a modern, scaleable and adaptable GIS-based monitoring system can take place are expressed here. This is followed by a case study, where I show the process of the development of such a GISbased monitoring system, the emerging problems and the solutions to these chosen by us, and the results obtained through this application.
Keywords: spatial informatics; recultivation; monitoring system